Insentif Pemutihan Denda Pajak dan Pembebasan Bea Balik Nama Kendaraan Bermotor: Meringankan atau Memanjakan? - Siti Karimah; Moh. Faisol (InFestasi, 2023)
The aim of this reseach to explore the perceptions of motor vehicle taxpayers in taking advantage of tax fines and exemption from motor vehicle transfer fees in Sumenep Regency. Using the case study method, the researcher conducted interviews with six informants. The research data was then analyzed using Miller Huberman's qualitative data analysis. The results of this study state that (1) for taxpayers who have tax arrears this policy is very helpful and lightens the tax burden that should be paid, because it is given relief from not paying tax penalties and exemption from transfer of title fees; (2) for taxpayers who do not have tax dependents, this policy does not provide education and even spoils taxpayers who are late or do not pay motor vehicle tax. Implications The implications of this research are that every policy taken by the government can always be considered in a comprehensive manner so that it does not only prioritize one interest, namely regional revenue, but also must understand the sociological conditions of the community.